2018
DOI: 10.3390/v10120678
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diaryl-Quinoline Compounds as Entry Inhibitors of Ebola Virus

Abstract: Ebola virus is the causative agent of Ebola virus disease in humans. The lethality of Ebola virus infection is about 50%, supporting the urgent need to develop anti-Ebola drugs. Glycoprotein (GP) is the only surface protein of the Ebola virus, which is functionally critical for the virus to attach and enter the host cells, and is a promising target for anti-Ebola virus drug development. In this study, using the recombinant HIV-1/Ebola pseudovirus platform we previously established, we evaluated a small molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…These secondary hits may potentially target other steps rather than RNA replication/transcription in the influenza virus replication cycle. Of note, cytotoxic compounds and luciferase inhibitors might also be initially identified as shared “hits”, where “toxic hits” can be excluded by a toxicity screening, while an orthogonal counterscreen using wild-type IAVs can exclude the small molecules that inhibit luciferase activity [40].…”
Section: Resultsmentioning
confidence: 99%
“…These secondary hits may potentially target other steps rather than RNA replication/transcription in the influenza virus replication cycle. Of note, cytotoxic compounds and luciferase inhibitors might also be initially identified as shared “hits”, where “toxic hits” can be excluded by a toxicity screening, while an orthogonal counterscreen using wild-type IAVs can exclude the small molecules that inhibit luciferase activity [40].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Cui and co-workers reported that diaryl-quinoline compounds are also active as entry inhibitors of EBOV [112].…”
Section: Ebola Virus Entry Inhibitorsmentioning
confidence: 99%
“…Recently, Cui and co-workers reported that diaryl-quinoline compounds are also active as entry inhibitors of EBOV [109].…”
Section: Miscellaneous Compounds That Inhibit Ebov Entrymentioning
confidence: 99%